Comparison between lateral sphincterometry and Lord’s operation in treatment of anal fissure - Velani, Yogesh V.; Velani, Attman P. (International Surgery Journal, 2019)
Background: Two widely performed surgeries include Lord’s anal dilatation (LAD) and lateral internal sphincterotomy (LIS). LAD is one of the ancient and simple surgical techniques, but with high incidence of recurrence and incontinences. LIS is the preferred surgical technique these days, but again with high incidence of incontinence. Aim of this study was done to compare LAD with LIS in the treatment of anal fissure with regard to symptoms, post-operative complications and recurrence. Methods: In the present study the age of patient was to be between 18–50 years, having CAF, all the patients having CAF not responded to the medical management for more than 6 weeks. The patients were randomly assigned to either group. Pre and post-operative pain was accessed using Wong-baker faces pain rating scale. Constipation was accessed by modified Longo score. Incontinence was accessed by scoring system reported by Wexner. Results: When the Wong Bakers faces pain score was done there were 69% of patients with grade IV score and 31% had grade V pain score. The second most presenting complaint was of bleeding per rectum, it was found in 80% of the patients. For constipation the preoperative modified Longo score was 14. On examination sentinel tag was present in all the cases out of which 93% was posterior, 5% anterior and multiple in 2% cases. Conclusions: A total of 200 patients were studied during the study. In this study, females were commonly affected than males. Constipation was the major predisposing factor among all cases 85%. Most of the fissures were located in the posterior midline 89%. Anterior fissures were slightly more common in females. It is our view that the role of pharmacological agents is likely to assume greater prominence in the future and that more effective agents and modes of delivery will be developed.